2010
DOI: 10.1080/02640411003628048
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and kinetic analysis of unilateral jumping in the vertical, horizontal, and lateral directions

Abstract: The aims of this study were to: (1) assess the reliability of various kinetic and temporal variables for unilateral vertical, horizontal, and lateral countermovement jumps; (2) determine whether there are differences in vertical ground reaction force production between the three types of jumps; (3) quantify the magnitude of asymmetry between limbs for variables that were established as reliable in a healthy population and whether asymmetries were consistent across jumps of different direction; and (4) establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 33 publications
6
63
2
8
Order By: Relevance
“…These specific demands could lead to the development of asymmetric adaptations between legs. The results in the present investigation were similar to other studies (Ceroni et al, 2012; Meylan et al, 2010), who found significant differences between limbs in unilateral jump capacity. Evidence in the existing literature is, however, equivocal as some previous research (Hewit et al, 2012; Schiltz et al, 2009) demonstrated no significant difference in unilateral vertical jump capacity in healthy athletes.…”
Section: Discussionsupporting
confidence: 93%
“…These specific demands could lead to the development of asymmetric adaptations between legs. The results in the present investigation were similar to other studies (Ceroni et al, 2012; Meylan et al, 2010), who found significant differences between limbs in unilateral jump capacity. Evidence in the existing literature is, however, equivocal as some previous research (Hewit et al, 2012; Schiltz et al, 2009) demonstrated no significant difference in unilateral vertical jump capacity in healthy athletes.…”
Section: Discussionsupporting
confidence: 93%
“…Correlation of the indices of all jumps (Table 4) has confi rmed already known facts from our and other authors' research [4,7,8,18,25], and also revealed some not very well-known causal relations. It was found that with the increase of body mass, duration of the takeoff phase becomes longer (r = 0.54, p<0.05) and body movement speed decreases (r = -0.45, p < 0.05).…”
Section: Research Results and Discussionsupporting
confidence: 59%
“…Its content is made up by biodynamic structure that is specifi c for different sport disciplines or teaching programmes; corresponding variety of movement forms reveals itself in work-out and competition conditions [1,2,[8][9][10]. Taking this into account, sports are systematized by special features:…”
Section: Introduction Theoretical Concept Of Sports Movementmentioning
confidence: 99%
See 2 more Smart Citations